2018
DOI: 10.1002/adem.201700960
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Austenitic Stainless Steels after Dynamic and Post‐Dynamic Recrystallization Treatment

Abstract: The effects of dynamic and post-dynamic recrystallization (DRX and post-DRX) on the microstructure and mechanical properties of austenitic stainless steels are critically reviewed. Particularly, the paper is focused on the grain refinement and strengthening by large strain deformation including severe plastic deformation conditions. The DRX and post-DRX microstructures are considered with close relation to the operative recrystallization mechanisms. Specific emphasis is placed upon two recrystallization mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 194 publications
2
14
0
Order By: Relevance
“…The flow stress can be expressed by a power law function of Z with an exponent of 0.2 in the range of low Z in Figure 3. This agrees well with other studies on hot working and creep at elevated temperatures, when the power law relationship generally holds between the flow stress and strain rate with a stress exponent of 5 [18,20]. In contrast, the temperature and/or strain rate effect on the flow stress diminishes with an increase in Z.…”
Section: Hot Deformation Behaviorsupporting
confidence: 91%
See 3 more Smart Citations
“…The flow stress can be expressed by a power law function of Z with an exponent of 0.2 in the range of low Z in Figure 3. This agrees well with other studies on hot working and creep at elevated temperatures, when the power law relationship generally holds between the flow stress and strain rate with a stress exponent of 5 [18,20]. In contrast, the temperature and/or strain rate effect on the flow stress diminishes with an increase in Z.…”
Section: Hot Deformation Behaviorsupporting
confidence: 91%
“…The absolute value of the grain size exponent in the relationship between D and σ ss decreases from 0.8 to 0.5 with an increase in the flow stress. Almost the same change in the grain size exponent has been observed in other austenitic steels subjected to warm deformation [2,18]. This change in the σ-D −N relationship has been attributed to the change in the DRX mechanism.…”
Section: Microstructures and Textures After Hot Compressionssupporting
confidence: 66%
See 2 more Smart Citations
“…Further analysis showed that both steels had practically identical microstructural features and, as a result, strength properties. The grain refinement by means of large strain deformation results commonly in substantial strengthening and significant degradation of plasticity (Tikhonova, Kaibyshev, & Belyakov, ). However, the present ultrafine‐grained (UFG) steels differ from other UFG alloys processed by severe plastic deformation by remarkable plasticity with total elongation above 15%.…”
Section: Discussionmentioning
confidence: 99%